The Ecology of Acidophilic Microorganisms in the Corroding Concrete Sewer Environment - Li, Xuan; Kappler, Ulrike; Jiang, Guangming; Bond, Philip L. (Frontiers in Microbiology, 2017)
Concrete corrosion is one of the most significant problems affecting valuable sewer infrastructure on a global scale. This problem occurs in the aerobic zone of the sewer, where a layer of surface corrosion develops on the exposed concrete and the surface pH is typically lowered from around 11-10 (pristine concrete) to pH 2-4. Acidophilic microorganisms become established as biofilms within the concrete corrosion layer and enhance the loss of concrete mass. Until recently, the acidophilic community was considered to comprise relatively few species of microorganisms, however, the biodiversity of the corrosion community is now recognized as being extensive and varying from different sewer environmental conditions. The diversity of acidophiles in the corrosion communities includes chemolithoautotrophs, chemolithoheterotrophs, and chemoorganohetertrophs. The activity of these microorganisms is strongly affected by H2S levels in the sewer gas phase, although CO2, organic matter, and iron in the corrosion layer influence this acidic ecosystem. This paper briefly presents the conditions within the sewer that lead to the development of concrete corrosion in that environment. The review focuses on the acidophilic microorganisms detected in sewer corrosion environments, and then summarizes their proposed functions and physiology, especially in relation to the corrosion process. To our knowledge, this is the first review of acidophilic corrosion microbial communities, in which, the ecology and the environmental conditions (when available) are considered. Ecological studies of sewer corrosion are limited, however, where possible, we summarize the important metabolic functions of the different acidophilic species detected in sewer concrete corrosion layers. It is evident that microbial functions in the acidic sewer corrosion environment can be likened to those occurring in the analogous acidic environments of acid mine drainage and bioleaching.